Peer support and skills training through an eating club for people with psychotic disorders: A feasibility study. (September 2019) - Vogel, Jelle Sjoerd; Swart, Marte; Slade, Mike; Bruins, Jojanneke; van der Gaag, Mark; Castelein, Stynke
Abstract: Objective: The HospitalitY (HY) intervention is a novel recovery oriented intervention for people with psychotic disorders in which peer support and home-based skill training are combined in an eating club. A feasibility study was conducted to inform a subsequent randomised trial. Methods: This study evaluated three eating clubs consisting of nine participants and three nurses. Semi-structured interviews and pre- and post-intervention measures (18 weeks) of personal recovery, quality of life and functioning were used to evaluate the intervention. Participants received individual skills training, guided by self-identified goals, while organising a dinner at their home. During each dinner, participants engaged in peer support, led by a nurse. Results: In personal interviews participants reported positive effects on social support, loneliness, and self-esteem. Nurses reported that participants became more independent during the intervention. Participants were satisfied with the HY-intervention (attendance rate = 93%). All were able to organise a dinner for their peers with practical support from a nurse. Pre- and post -intervention measures did not show important improvements. Limitations: Outcome measures were not sensitive to change, likely due to a short intervention period (5 months) and a limited number of participants (N = 9). Using Goal Attainment Scaling to evaluate personal goals turned out to be unfeasible. Conclusions: The HY-intervention is feasible for participants with psychotic disorders. This study refined intervention and research design for the upcoming multicentre randomised controlled trial. We expect that the Experience Sampling Method will be more sensitive to changes in recovery outcomes than regular pre-post intervention measures. Highlights: Many patients with psychotic disorders experience a lack of social connection. Skills training at home, compared to a clinic, generalises better to daily life. Eating clubs are feasible in people with psychotic disorders. A home-based, peer supported setting motivates to work on personal goals. An eating club could lead to positive effects on personal recovery themes.